Edukasi Anemia Defisiensi Besi pada Remaja Putri di Pesantren Al Hidayah - Tina Yuli Fatmawati; Andicha Gustra Jeki; Nel Efni; Siti Fati Hatussaadah (Universitas Baiturrahim, 2026)
Anemia is a public health problem in Indonesia that affects all age groups, from toddlers to the elderly. In 2018, 32% of Indonesian adolescents suffered from anemia, and it is estimated that the majority of anemia is due to iron deficiency resulting from insufficient intake of iron-rich foods, particularly animal-based foods. Iron deficiency anemia is most common in adolescent girls due to excessive blood loss during menstruation, and their iron needs increase during puberty. This puts them at risk of decreased immunity, impaired concentration in learning, and complications during pregnancy. The purpose of this community service is to increase adolescent girls' knowledge about iron deficiency anemia. The methods used in this activity include discussion, mentoring, and persuasive communication. The target group for this community service were 25 adolescent girls from the Al Hidayah Islamic Boarding School. The results showed an increase in the adolescent girls' knowledge about iron deficiency, from an average of 78% to 97%. The adolescent girls are advised to actively seek information about the dangers of anemia and to pay attention to their nutritional intake to avoid anemia